CXCR4 Antagonist AMD3100 Promotes Cardiac Functional Recovery After Ischemia-Reperfusion Injury via eNOS-Dependent Mechanism - Jujo, Kentaro (2012)
BACKGROUND: CXC-chemokine receptor 4 (CXCR4) regulates the retention of stem/progenitor cells in the bone marrow (BM), and the CXCR4 antagonist AMD3100 improves recovery from coronary-ligation injury by mobilizing stem/progenitor cells from the BM to the peripheral blood. Thus, we investigated whether AMD3100 also improves recovery from ischemia-reperfusion (IR) injury, which more closely mimics myocardial infarction in patients, because blood flow is only temporarily obstructed. METHODS AND RESULTS: Mice were treated with single subcutaneous injections of AMD3100 (5 mg/kg) or saline after IR injury. Three days later, histological measurements of the infarct-area/area-at-risk ratio were smaller in AMD3100-treated mice than in mice administered saline, and echocardiographic measurements of left-ventricular function were greater in the AMD3100-treated mice at week 4. CXCR4+ cells were mobilized for just 1 day in both groups, but the mobilization of sca1+/flk1+ cells endured for 7days in AMD3100-treated mice compared to just 1 day in the saline-treated mice. AMD3100 upregulated BM levels of endothelial nitric oxide synthase (eNOS) and two targets of eNOS signaling, matrix-metalloproteinase 9 and soluble Kit ligand. Furthermore, the loss of BM eNOS expression abolished the benefit of AMD3100 on sca1+/flk1+ cell mobilization without altering the mobilization of CXCR4+ cells, and the cardioprotective effects of AMD3100 were retained in eNOS-knockout mice that had been transplanted with BM from wild-type mice, but not in wild-type mice with eNOS-knockout BM. CONCLUSIONS: AMD3100 prolongs BM progenitor mobilization and improves recovery from IR injury, and these benefits appear to occur through a previously unidentified link between AMD3100 and BM eNOS expression.